2021
DOI: 10.1186/s13287-021-02551-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectivity of mesenchymal stem cells for bleomycin-induced pulmonary fibrosis: a systematic review and implication for clinical application

Abstract: Pulmonary fibrosis (PF) is a chronic, progressive, fibrotic interstitial disease of the lung with poor prognosis and without effective treatment currently. Data from previous coronavirus infections, such as the Severe Acute Respiratory Syndrome (SARS) and Middle East Respiratory Syndrome, as well as current clinical evidence from the Coronavirus disease 2019 (COVID-19), support that SARS-CoV-2 infection may lead to PF, seriously impacting patient prognosis and quality of life. Therefore, effective prevention a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…Clinical trials have shown that intravenous MSCs are effective and safe for treating patients with severe IPF, improving lung function and fibrosis scores under CT, and increasing the 6-min walk distance. The most common source of MSCs in clinical trials of MSCs as IPF treatment is the bone marrow [ 15 ]. After transplantation, BMSCs can migrate to damaged lung tissues, modulate immune cell function, reduce local inflammation, and inhibit fibrosis through various pathways such as paracrine secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials have shown that intravenous MSCs are effective and safe for treating patients with severe IPF, improving lung function and fibrosis scores under CT, and increasing the 6-min walk distance. The most common source of MSCs in clinical trials of MSCs as IPF treatment is the bone marrow [ 15 ]. After transplantation, BMSCs can migrate to damaged lung tissues, modulate immune cell function, reduce local inflammation, and inhibit fibrosis through various pathways such as paracrine secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cell (MSC) transplantation is a new approach to treating PF [ 14 ]. These cells can reduce the inflammatory response, promote epithelial repair, and reduce the deposition of pulmonary extracellular matrix in PF lung tissues through multidirectional differentiation, immune regulation, and paracrine functions [ 15 ]. Astragalus and its metabolites can promote the proliferation, differentiation, and migration of MSCs [ 16 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…SASP factors can lead to abnormal wound healing, characterized by abnormal crosstalk between epithelial and mesenchymal cells, and the subsequent accumulation of myofibroblasts [6]. It has been observed that fibroblasts and myofibroblasts in fibrotic lungs show signs of stress and senescence, including resistance to apoptosis and excessive production of extracellular matrix components [13]. Moreover, fibrosis could result from this increase in matrix stiffness, which leads to irreversible tissue damage [14].…”
Section: Introductionmentioning
confidence: 99%
“…Collectively stating that fibrosis of the lungs is a chronic, progressive, fibrotic interstitial disease with a poor prognosis [15]. Currently, it has no effective treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation